Vagus nerve stimulation rate and duration determine whether sensory pairing produces neural plasticity - Buell, Elizabeth P. (Neuroscience, 2019)
Repeatedly pairing a brief train of vagus nerve stimulation (VNS) with an auditory stimulus drives reorganization of primary auditory cortex (A1). A number of studies document that the stimulation parameters of VNS, including intensity and pulse rate, regulate the magnitude of VNS-dependent cortical plasticity. However, there is currently little data to guide the selection of VNS train durations, an easily adjusted parameter that could influence the effect of VNS-based therapies. Here, we tested the effect of varying the duration of the VNS train on the extent of VNS-dependent cortical plasticity. Rats were exposed to a 9 kHz tone 300 times per day for 20 days. Coincident with tone presentation, groups received trains of 4, 16, or 64 pulses of VNS delivered at 30 Hz, corresponding to train durations of 0.125 s, 0.5 s, and 2.0 s, respectively. High-density microelectrode mapping of A1 revealed that 0.5 s duration VNS trains significantly increased the number of neurons in A1 that responded to tones near the paired tone frequency. Trains lasting 0.125 or 2.0 s failed to alter A1 responses, indicating that both shorter and longer stimulation durations are less effective at enhancing plasticity. A second set of experiments evaluating the effect of delivering 4 or 64 pulses in a fixed 0.5 s VNS train duration paired with tone presentation reveal that both slower and faster stimulation rates are less effective at enhancing plasticity. We incorporated these results with previous findings describing the effect of stimulation parameters on VNS-dependent plasticity and activation of neuromodulatory networks to generate a model of synaptic activation by VNS. The findings from the present study may facilitate determination of optimal parameters for clinical implementation of VNS therapies.